2004
DOI: 10.1038/sj.gt.3302413
|View full text |Cite
|
Sign up to set email alerts
|

T-cell engineering by a chimeric T-cell receptor with antibody-type specificity for the HIV-1 gp120

Abstract: Immune-based approaches of cell therapy against viral pathogens such as the human immunodeficiency virus type 1 (HIV-1) could be of primary importance for the control of this viral infection. Here, we designed a chimeric cell surface receptor (105TCR) to provide primary human T-lymphocytes with antibody-type specificity for the HIV-1 envelope glycoprotein. This receptor includes the single chain Fv domain of the neutralizing anti-gp120 human monoclonal antibody F105, CD8a hinge and the transmembrane and the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 62 publications
0
39
0
Order By: Relevance
“…[7][8][9][10][11] Because residual HIV expression continues despite effective ART [12][13][14][15][16] and is required for viral rebound, HIV-infected cells should theoretically be targetable by a T cell therapeutic agent. Several mechanisms are thought to be responsible for the apparent failure of autologous cytotoxic T lymphocytes (CTLs) to clear reactivated cells in HIV-infected individuals: HIV evolution prior to ART quickly selects for CTL escape mutations; [17][18][19] HIV Nef mediates downregulation of major histocompatibility complex class I (MHC-I), 20,21 protecting HIV-infected cells from T cell receptor (TCR)-dependent CTL killing; and HIV-specific CTL responses may be limited by exhaustion 22,23 or peripheral immune tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Because residual HIV expression continues despite effective ART [12][13][14][15][16] and is required for viral rebound, HIV-infected cells should theoretically be targetable by a T cell therapeutic agent. Several mechanisms are thought to be responsible for the apparent failure of autologous cytotoxic T lymphocytes (CTLs) to clear reactivated cells in HIV-infected individuals: HIV evolution prior to ART quickly selects for CTL escape mutations; [17][18][19] HIV Nef mediates downregulation of major histocompatibility complex class I (MHC-I), 20,21 protecting HIV-infected cells from T cell receptor (TCR)-dependent CTL killing; and HIV-specific CTL responses may be limited by exhaustion 22,23 or peripheral immune tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have described the generation of HIV-1-specific CAR-T cells by connection of an extracellular antigenbinding domain to intracellular T cell activation domains (e.g., CD3 and CD28). The former can be a single-chain variable fragment (scFv) (26)(27)(28)(29)(30) or a natural molecule, such as CD4 (26,27,(31)(32)(33)(34)(35)(36), capable of directly inducing the death of cells expressing the viral envelope glycoprotein (Env). However, it remains to be determined whether these CAR-T cells can be used to kill the reactivated HIV-1 latently infected cells from the infected individuals receiving suppressive cART.…”
mentioning
confidence: 99%
“…The receptor specificity is determined by extracellular single-chain fragments of the variable region (scFv) that recognize predefined antigens and can easily be altered by selecting an appropriate scFv (16). Recombinant immunoreceptors have been successfully developed against a number of tumor antigens (16) but against only a few viral proteins from HIV and hepatitis B virus (6,20,22) and not against CMV.…”
Section: Cytomegalovirus (Cmv) Infection In Patients Receiving Hematomentioning
confidence: 99%
“…The receptor specificity is determined by extracellular single-chain fragments of the variable region (scFv) that recognize predefined antigens and can easily be altered by selecting an appropriate scFv (16). Recombinant immunoreceptors have been successfully developed against a number of tumor antigens (16) but against only a few viral proteins from HIV and hepatitis B virus (6,20,22) and not against CMV.In human CMV infection, the analysis of the physiological cytotoxic T lymphocyte (CTL) response has been focused on a limited set of proteins, namely, the proteins pp65, IE1, and IE2; recent and more extensive studies have shown that glycoprotein B (gB) as well as other CMV glycoproteins is also able to evoke adaptive T cell responses (32, 34). Notably, the CMV gB is expressed at the cell surface during the early or delayed early phase of CMV replication, even in the presence of clinically used inhibitors of viral DNA replication (33).…”
mentioning
confidence: 99%